Mast cells in lung of rat - I. Ivanova (Trakia Journal of Sciences)
This paper is a short review of scientific literature on lung mast cells in norm and pathology that shows the current state of this problem. Particular attention is paid to the quantity, location and arrangement of the mast cells. The mast cells are a part of immune system whom origin are myeloid stem cells. They are a kind of white blood cells. Many authors from the 19th century to the present day have traced and described the role of mast cells in the human body, their structure and changes depending on the functional state of the organism. Paul Ehrlich is the first author that described in his doctoral thesis the mast cells as effectors of allergy particularly in the beginning of reaction and in acute phase of the process. Research has continued through out the 20th century and researchers' efforts are primarily focused on clarifying the structure and function of mast cells and identifying their role in pathological responses in the human body. Mast cells are found in all organs, but they predominate in peripheral blood, spleen and bone marrow. There are cells in the rat skin that live for about 12 weeks, and more recent studies have found that proliferation of mature mast cells is caused by various factors.